Food and Beverage Sanitation Hygiene Monitoring and Food Quality Served by Traders in the Elementary School Environment, Alafan District, Simeulue Regency - Fitri Rahma Yunita; Ihsan Murdani (Jurnal EduHealth, 2023)
Food is a basic need for human life. Cases of food poisoning and infectious diseases due to food tend to increase. Children often become victims of the disease. One of the reasons is due to not paying attention to personal hygiene and the environment in the process of food management. Food hygiene and sanitation supports the prevention of food poisoning. The purpose of this study was to monitor Food and Beverage Sanitation Hygiene and the Quality of Food Served by Traders in the Elementary School Environment, Alafan District, Simeulue Regency. The method used in analyzing and studying is observational with a descriptive approach, namely wanting to know the conditions of food and drinks sold in elementary school canteens in terms of sanitary hygiene. This research is an observational study with a descriptive approach, namely wanting to know the conditions of food and drinks sold in elementary school canteens in terms of sanitary hygiene. The results of this study indicate that the hygiene description of snack food handlers in the elementary school environment, Alafan District, Simeulue Regency shows that the hygiene of all handlers does not meet the requirements. The description of the sanitation of snack food equipment in the elementary school environment in Alafan District, Simeulue Regency shows that only 2 canteens meet the hygiene and sanitation requirements for snacks in the canteen in the elementary school environment in Alafan District, Simeulue Regency. The description of the sanitation of serving snacks in the elementary school environment in Alafan District, Simeulue Regency shows that the sanitation of serving food in all canteens (75%) does not meet the requirements. The description of the sanitation of the snack food vendor facilities in the elementary school environment, Alafan District, Simeulue Regency shows that out of 4 canteens, only 1 canteen fulfills the sanitation requirements for serving this because the canteen owners do not pay attention to the serving container as what is sold must be wrapped and closed and avoid contamination. vector (disease-carrying flies) shows that the sanitation of the vendor facilities in 2 canteens (70%) does not meet the requirements. only 1 canteen fulfills the sanitation requirements for serving this because the canteen owners do not pay attention to the serving container as what is sold must be wrapped and closed and avoid contamination. vector (disease-carrying flies) shows that the sanitation of the vendor facilities in 2 canteens (70%) does not meet the requirements. only 1 canteen fulfills the sanitation requirements for serving this because the canteen owners do not pay attention to the serving container as what is sold must be wrapped and closed and avoid contamination. vector (disease-carrying flies) shows that the sanitation of the vendor facilities in 2 canteens (70%) does not meet the requirements.